Prospective associations between occupational physical activity level and sleep disturbances: a five-year follow-up study - Yun-Han Wang; Chien-Fong Huang; Li-Jung Chen; Po-Wen Ku; Emmanuel Stamatakis (BMC Public Health)
Abstract Background Sleep disturbances are commonly reported in working populations. While research has identified various work-related risk factors for poor sleep, the relationship between prior occupational physical activity (OPA) and future sleep disturbances remains unclear. The study aimed to examine the prospective associations between OPA levels and sleep disturbances in adults. Methods We utilized longitudinal data from the MJ cohort study (1998 to 2022). The sample (N = 62528) consisted of adults aged 18 years or above. The mean age (in years) was 35.9 (SD = 9.5), and they were working full-time and reported no sleep disturbances at baseline. We examined the prospective associations between self-reported OPA levels (light, moderate, moderately heavy, and heavy) at baseline, and the presence of sleep disturbances at a mean follow-up time of 5.6 years (SD = 4.5). Cox proportional hazard models were conducted, adjusting for potential confounding variables. Results Using light OPA level as the reference group, individuals with moderately heavy OPA (HR: 1.13, 95% CI: 1.07, 1.19, p < 0.001) and heavy OPA (HR: 1.22, 95% CI: 1.11, 1.34, p < 0.001) at baseline had a higher risk of sleep disturbances at follow-up. Stratified analyses showed that the association between higher levels of OPA and sleep disturbances remained across different subgroups. Notably, these associations were more pronounced among females (p interaction = 0.008), for moderately heavy OPA (HR: 1.23, 95% CI: 1.12, 1.35, p < 0.001) and heavy OPA (HR: 1.45, 95% CI: 1.10, 1.91, p = 0.009). These associations were also more pronounced in certain occupational groups (p interaction = 0.003), where only heavy OPA was significantly associated with an elevated risk of sleep disturbances among civil servants (HR: 1.66, 95% CI: 1.08, 2.55, p = 0.020) and office workers, professionals and technicians (HR: 1.49, 95% CI: 1.09, 2.05, p = 0.010). Conclusions Higher OPA levels were associated with an increased risk of sleep disturbances. Workplace support or interventions are in need to improve sleep patterns.